BS ISO 4586-5. High-pressure decorative laminates (HPL, HPDL). Sheets based on thermosetting resins (usually called laminates). Part 5. Classification and specifications for flooring grade laminates less than 2 mm thick intended for bonding to supporting substrates (10th March 2020) - British Standards Institution,
No abstract available